Relevansi Nilai-nilai Pendidikan Agama Islam dengan Program Kegiatan Pramuka di SMK Negeri 1 Kerinci - Jannah, Miftahul; Wiza, Rahmi (ALSYS, 2024)
The lack of Islamic religious education lesson hours, which is only 3 lesson hours per week at the SMK/MAK level, plus Prakerind (Industrial Work Practice) for 2 semesters, is of course not enough for a PAI teacher to teach a very broad PAI material. This research aims to determine the relationship between the values of Islamic religious education and the scout activity program at SMK N 1 Kerinci. It is hoped that once the connection between PAI values and scout activities is known, students will be interested in taking part in scout activities to learn and implement PAI values outside of class hours. This research uses a qualitative method with a case study type of research, the object of this research is the scout members of SMK N 1 Kerinci. The data in this research was obtained from observation, interviews and documentation. In analyzing the data the author used source triangulation. The results of this research show that there is a connection between the values of Islamic religious education in several Scout activity programs at SMK N 1 Kerinci. In the scout activity program implemented there are two values of Islamic religious education, namely the value of worship, including: congregational prayer, du'a, natural tadabur, muhasabah, and mutual help. Then the moral values include: Discipline, Patience, Politeness, Independence, Leadership, Willing to help. The habit of worshiping and cultivating these character values can improve the religious attitudes of Scout members.